PERANAN MODAL SOSIAL DALAM PENGELOLAAN BADAN USAHA MILIK DESA (BUM Desa) (Studi di Desa Karangrejek Kecamatan Wonosari dan Desa Bleberan Kecamatan Playen Kabupaten Gunungkidul) - R. RACHMAWATI, R. RACHMAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Social capital roles as the adhesive that binds all people in society. Social capital is an important issue in the success of an organization. But not only armed with a mere financial capital, but also need the support of human resources and social capital. So in the management of the BUM Desa, social capital is needed, social capital grows because of kinship, togetherness, and the attitude of helping each other between the members of society. Social capital refers to the main aspects of social organization such as trust, norms, network that is able to mobilize the participation of rural communities to achieve a common goal. In this study the author looks at the potential of social capital in the villages continuosly preserved and has formed a collective consciousness of society. The formulation of this research is how the dynamics of social capital as well as the contribution and role of social capital owned by the village community in Karangrejek Village and Bleberan Village in the management of BUM Desa. The objective of this study is to determine the dynamics of the social capital held by society of Karangrejek Village and Bleberan Village in the management of the BUM Desa and determine the contribution and role of social capital on the management of the BUM Desa in those two villages. The method used to address the above problem is qualitative, with purposive sampling technique, to obtain the data naturally, by conducting field research. Data analysis techniques were analyzed qualitatively, based on the support of the theory associated with the object of research of informa nts by interview, observation and documentation. Then drawn a conclusion about the results of research. The findings in this study is the author getting three -stage process dynamics of social capital in managing of BUM Desa in Karangrejek Village and Bleberan village, named the reconstruction phase, the transition phase, and the maturity phase. The dynamics of social capital in the two villages have different characteristics, BUM Desa Karangrejek village formed with human resources excellence more emphasis on the quality of public services. While the BUM Desa Bleberan Village formed because it has the advantage of natural resources and business-oriented (profit-oriented). The role of social capital which was originally only the adhesive public life in the two villages, but the formation of BUM Desa, social capital is key for the people to improve their living standards in order to achieve a more orderly life and prosperity through efforts with BUM Desa.